The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10327-008-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen application at anthesis on Fusarium head blight and mycotoxin accumulation in breadmaking wheat in the western part of Japan

Abstract: In the western part of Japan, two wheat cultivars, Nishinokaori and Minaminokaori, are currently cultivated for breadmaking. Breadmaking wheat requires a higher protein content compared to the Japanese noodle wheat (the major type of wheat in Japan). This high protein level in the grain is obtained by top-dressing with nitrogen (N) near anthesis. Because such N applications may increase levels of Fusarium head blight (FHB) and consequent mycotoxin [deoxynivalenol (DON) and nivalenol (NIV)] accumulation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
1
19
2
Order By: Relevance
“…incidence. Several recent studies have shown that FHB infection and Fusarium mycotoxin contaminations were increased with higher rate of N application (Lemmens et al 2004;Burgt et al 2011), whereas other studies did not reveal any significant effects of N application on FHB (Váňová et al 2008;Yoshida et al 2008). …”
Section: Discussionmentioning
confidence: 95%
“…incidence. Several recent studies have shown that FHB infection and Fusarium mycotoxin contaminations were increased with higher rate of N application (Lemmens et al 2004;Burgt et al 2011), whereas other studies did not reveal any significant effects of N application on FHB (Váňová et al 2008;Yoshida et al 2008). …”
Section: Discussionmentioning
confidence: 95%
“…FHB was assessed at 20 DAA in both years (ZGS 77; late milk stage). Fifty spikes were arbitrarily selected from each plot and assessed for FHB severity on a scale of 0 to 100 (scores of 0, 5,10,20,30,40,50,60,70,80,90, and 100, according to visual rating of the percentage of discolored area of the spike), as in previous studies (47,49), and the average was calculated for each plot. Using these data, FHB incidence (percentage; i.e., the percentage of visually diseased spikes) was also calculated for each plot.…”
Section: Methodsmentioning
confidence: 99%
“…Excessive nitrogen fertilization results in a decreased carbohydrate level in cultivated plants and it also may be a reason for the limited resistance to some fungal diseases (Yoshida et al 2008;Huber and Thompson 2007). Rice blast (Kürschner et al 1992;Long et al 2000) is the best-known example of such a disease.…”
Section: Effect Of Abiotic Stress On Carbohydrate Content and Resistamentioning
confidence: 99%